2005
DOI: 10.1074/jbc.m411151200
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescence Resonance Energy Transfer Reveals Ligand-induced Conformational Changes in CXCR4 Homo- and Heterodimers

Abstract: Homo-and heterodimerization have emerged as prominent features of G-protein-coupled receptors with possible impact on the regulation of their activity. Using a sensitive bioluminescence resonance energy transfer system, we investigated the formation of CXCR4 and CCR2 chemokine receptor dimers. We found that both receptors exist as constitutive homo-and heterodimers and that ligands induce conformational changes within the pre-formed dimers without promoting receptor dimer formation or disassembly. Ligands with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
237
3
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 237 publications
(269 citation statements)
references
References 59 publications
26
237
3
3
Order By: Relevance
“…Recent evidence shows that chemokines interfere with MOR and KOR antinociceptive activity [49,50]. CXCR4 forms homo- [22,51] and heterodimers [38,52] at the cell surface. Our data are compatible with a model in which the receptor conformation stabilized depends on several factors including (i) receptor levels at the cell surface, (ii) ligand levels in the cell microenvironment, and (iii) the presence of other factors that alter receptor or ligand expression and function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent evidence shows that chemokines interfere with MOR and KOR antinociceptive activity [49,50]. CXCR4 forms homo- [22,51] and heterodimers [38,52] at the cell surface. Our data are compatible with a model in which the receptor conformation stabilized depends on several factors including (i) receptor levels at the cell surface, (ii) ligand levels in the cell microenvironment, and (iii) the presence of other factors that alter receptor or ligand expression and function.…”
Section: Discussionmentioning
confidence: 99%
“…The results confirmed that DOR-CXCR4 complexes also form in primary cells in a ligand-independent manner. Many reports show that CXCR4 and DOR form homoand heterodimers [8,10,22,37,38]. To determine whether these conformations are fixed or in dynamic equilibrium, we cotransfected HEK293 cells with CXCR4-CFP, CXCR4-YFP and increasing amounts of DOR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ce résultat contredit nos observations initiales d'un blocage de CXCR4 par ces substances. À l'aide de la technique TIRF, nous avons montré que les récepteurs CXCR4 ne forment pas de dimères lorsqu'ils sont exprimés à la membrane des ovocytes de xénope, contrairement à ce qui est décrit dans les cellules de mammifères [14,15]. Nous avons alors utilisé un autre système cellulaire, les cellules Nous avons d'abord pensé que les récep-teurs GABA B et CXCR4 pouvaient interagir dans la membrane des cellules : en effet, on sait que CXCR4 peut former des hétérodimères avec d'autres récepteurs couplés aux protéines G [12,13].…”
Section: Le Baclofène Est Un Modulateur Allostérique Du Récepteur Cxcr4unclassified
“…Toutefois, il exclut clairement les antagonistes de CXCR4 de l'arsenal antirétroviral, dans une perspective de thérapie permanente, à moins que l'on ne soit en mesure de [27]. Grâce à cette technique, notre équipe a démontré que CXCR4 forme un homodimère constitutif [28]. De plus, nous avons établi que l'application de différents ligands naturels et synthétiques sur le dimère de récepteur module le BRET qui en résulte, ce qui permet l'observation des changements conformationnels du récepteur induits par ces ligands.…”
Section: Cxcr4 Cible Thérapeutique Prometteuse Mais Délicateunclassified